The evolutionary journey to a new normal for learning and capacity building of healthcare workers to prepare and respond to health emergencies across Africa - Bonkoungou, Boukaré; Mosha, Fausta; Abianuru, Amarachi; Okeibunor, Joseph; Utunen, Heini; Balaciano, Giselle; Barbosa de Lima, Ana C.; Burke, Lauren; McKenna, Shannon; Nag, Sukriti; Gueye, Abdou Salam; Struminger, Bruce (Frontiers in Public Health, 2025)
BackgroundFaced with the COVID-19 mobility restrictions, the WHO AFRO EPR program pioneered a collaborative initiative with Project ECHO to virtually educate health workers across Africa at scale. This initiative has evolved into a transformative learning journey. This paper aims to present the lessons learned.ResultsFrom April 2020 to February 2024, 287 virtual learning sessions were conducted with over 125,816 attendances from 173 countries and regions. This marked a significant increase compared to pre-pandemic face-to-face training, which targeted fewer than 2,000 participants annually. Survey responses (n = 43,221) indicated high relevance and applicability, with 97% of respondents planning to use the information in their work and 89% finding the sessions very or extremely relevant. Self-reported knowledge levels increased from 28 to 74% post-session.DiscussionIntegrating digital learning into WHO AFRO's education and training toolkit has facilitated immediate emergency responses and enhanced long-term resilience, adaptability, and equity among healthcare workers, especially in under-resourced regions. This initiative has reached more health professionals than pre-pandemic in-person training, facilitating more equitable access to essential knowledge and best practices.ConclusionThe WHO AFRO and Project ECHO partnership navigated a variety of challenges, while establishing a paradigm shift in learning strategies. Emphasizing a digital learning first approach, while retaining in-person elements, this collaborative initiative offers insights for future healthcare education, highlighting adaptability, cost-efficiency, equity, and new technologies in addressing global health challenges. However, to sustain this momentum and further expand access to critical knowledge, stakeholders must commit to continued investment in digital learning infrastructure, training, and technology.